Data from: Y-chromosome markers for the red fox - Rando, Halie M.; Stutchman, Jeremy T.; Bastounes, Estelle R.; Johnson, Jennifer L.; Driscoll, Carlos A.; Barr, Christina S.; Trut, Lyudmila N.; Sacks, Benjamin N.; Kukekova, Anna V. (Dryad, 2017)
The de novo assembly of the red fox (Vulpes vulpes) genome has facilitated the development of genomic tools for the species. Efforts to identify the population history of red foxes in North America have previously been limited by a lack of information about the red fox Y-chromosome sequence. However, a megabase of red fox Y-chromosome sequence was recently identified over 2 scaffolds in the reference genome. Here, these scaffolds were scanned for repeated motifs, revealing 194 likely microsatellites. Twenty-three of these loci were selected for primer development and, after testing, produced a panel of 11 novel markers that were analyzed alongside 2 markers previously developed for the red fox from dog Y-chromosome sequence. The markers were genotyped in 76 male red foxes from 4 populations: 7 foxes from Newfoundland (eastern Canada), 12 from Maryland (eastern United States), and 9 from the island of Great Britain, as well as 48 foxes of known North American origin maintained on an experimental farm in Novosibirsk, Russia. The full marker panel revealed 22 haplotypes among these red foxes, whereas the 2 previously known markers alone would have identified only 10 haplotypes. The haplotypes from the 4 populations clustered primarily by continent, but unidirectional gene flow from Great Britain and farm populations may influence haplotype diversity in the Maryland population. The development of new markers has increased the resolution at which red fox Y-chromosome diversity can be analyzed and provides insight into the contribution of males to red fox population diversity and patterns of phylogeography. Raw Fragment Analysis DataThis is all of the raw data generated and analyzed for the development of a 13-microsatellite marker panel for the red fox Y-chromosome. It may be useful to researchers looking to calibrate calls made in new samples/populations using these markers. This zipped file includes all original .abi files, raw allele calls and peaks as produced with GeneMapper v3.5, a table of the final allele ...